Personalized Nutrition Advice: Preferred Ways of Receiving Information Related to Psychological Characteristics - Dijksterhuis, Garmt B.; Bouwman, Emily P.; Taufik, Danny (Frontiers in Psychology, 2021)
The primary goal of this paper is to draw upon several psychological personality theories in an attempt to distinguish unique underlying factors that can subsequently be used to personalise nutrition information for consumers to ultimately stimulate healthy eating. A secondary goal is to explore the relation between the identified factors and consumers’ preferences for receiving certain forms of dietary advice/information. A number of general psychological scales (self-regulation, action and coping self-efficacy, social comparison, intrinsic motivation, health info processing, need for cognition and for affect, and regulatory focus) is used to distinguish dimensions underlying 1013 consumers’ preferences for receiving personalised forms of nutrition advice to stimulate healthy eating. The set of joint items is analysed using a Principal Component Analysis to find underlying psychological characteristics. These characteristics are used to predict preferences for receiving nutrition and health information, using a Logistic Regression. The PCA produces four components (explaining 51% of variation), that could be interpreted as ‘intrinsic interest and capabilities for healthy eating’, ‘perceived difficulty to eat healthily’, ‘self-worth insecurity’ and ‘seeking positive challenges’, respectively. By means of a Logistic Regression these components are able to predict preferences for different ways of receiving nutrition advice. There appear different personalities of consumers, that may benefit by being addressed according to their preference for receiving nutrition advice on specific moments, of a specific level of detail or pointing at the type of consequences the advice has.